2016
DOI: 10.1021/acs.biochem.6b00163
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Biomineralization Phenomena Created by a Combinatorial Nacre Protein Model System

Abstract: In the nacre or aragonite layer of the mollusk shell there exist proteomes which regulate both the early stages of nucleation and nano-to-mesoscale assembly of nacre tablets from mineral nanoparticle precursors. Several approaches have been developed to understand protein-associated mechanisms of nacre formation, yet we still lack insight into how protein ensembles or proteomes manage nucleation and crystal growth. To provide additional insights we have created a proportionally-defined combinatorial model cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
124
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(135 citation statements)
references
References 55 publications
10
124
1
Order By: Relevance
“…These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion. What was discovered was very informative: these proteins are distinguishable in terms of what mineral species or steps in the non-classical scheme they affect (Figure 4) [58][59][60][61][62][63][64][65][66][67]. Further, using mineralization assays which overlap with the time periods of the potentiometric titrations and utilize similar solution and supersaturation conditions [58][59][60][61][62][63][64][65][66][67] these studies demonstrated that these proteins form hydrogels that can capture, assemble, and organize mineral nanoparticles ( Figure 5) [62,65] consistent with CPA theory [15].…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion. What was discovered was very informative: these proteins are distinguishable in terms of what mineral species or steps in the non-classical scheme they affect (Figure 4) [58][59][60][61][62][63][64][65][66][67]. Further, using mineralization assays which overlap with the time periods of the potentiometric titrations and utilize similar solution and supersaturation conditions [58][59][60][61][62][63][64][65][66][67] these studies demonstrated that these proteins form hydrogels that can capture, assemble, and organize mineral nanoparticles ( Figure 5) [62,65] consistent with CPA theory [15].…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 98%
“…As an example, recent in vitro studies involving five recombinant mollusk shell nacre-associated proteins [58][59][60][61][62][63][64][65][66] and ACC-stabilizing sea urchin spicule matrix proteins [67,68] have utilized mineralization assay conditions identical to those employed in non-classical nucleation studies [29][30][31][32][33]. What links these different biomineralization proteins together are two common molecular themes [69,70]: intrinsic disorder, or absence of folding protein structure, and amyloid-like aggregation-prone domains, which promote protein-protein association leading to the formation of protein phases or hydrogels [58][59][60][61][62][63][64][65][66][67][68]. These reported studies utilized mole protein quantities, Ca(II) potentiometric methods, and parallel mineralization assay systems to study the early and later events in calcite-based calcium carbonate nucleation and monitor the formation and stabilization of PNCs and ACC in a time-dependent fashion.…”
Section: Moving Towards More Informative Studiesmentioning
confidence: 99%
See 3 more Smart Citations